2016
DOI: 10.1016/j.biopsych.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Psychosocial Treatment With D-Cycloserine: Models, Moderators, and Future Directions

Abstract: Advances in the understanding of the neurobiology of fear extinction resulted in the development of d-cycloserine (DCS), a partial glutamatergic N-methyl-D-aspartate agonist, as an augmentation strategy for exposure treatment. We review a decade of research that has focused on the efficacy of DCS for augmenting the mechanisms (e.g., fear extinction) and outcome of exposure treatment across the anxiety disorders. Following a series of small-scale studies offering strong support for this clinical application, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 86 publications
(112 reference statements)
3
61
1
Order By: Relevance
“…These results are consistent with studies of other anxiety disorders that have shown an acceleration of treatment response with DCS augmentation, observed in the absence of an endpoint advantage when longer protocols of treatment are used 19; 20 . In contrast, endpoint advantages for DCS are more consistently observed when especially brief treatments are used, in line with the hypothesis that endpoint advantages are primarily seen when the placebo-augmented group does not have additional exposure sessions to allow them to catch up, in terms of response, to the DCS-augmented group 15 .…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…These results are consistent with studies of other anxiety disorders that have shown an acceleration of treatment response with DCS augmentation, observed in the absence of an endpoint advantage when longer protocols of treatment are used 19; 20 . In contrast, endpoint advantages for DCS are more consistently observed when especially brief treatments are used, in line with the hypothesis that endpoint advantages are primarily seen when the placebo-augmented group does not have additional exposure sessions to allow them to catch up, in terms of response, to the DCS-augmented group 15 .…”
Section: Introductionsupporting
confidence: 66%
“…There is increasing evidence that DCS augmentation has a primary action of speeding treatment response 15 . The current study fits this pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these trials have been conducted in adults. Additional research is needed to better understand the nuances of augmenting CBT with cognitive enhancers in youth [25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…The most promise may come from the glutaminergic NMDA agonist d-cycloserine that has shown promising results in the treatment of anxiety disorders with respect to fear extinction [87]. One study tested this substance in AN in order to facilitate eating in a laboratory design and found that d-cycloserine was associated with greater caloric intake compared to no medication [88].…”
Section: Medication Studies In Anmentioning
confidence: 99%